In Vitro and In Vivo Performance Testing of a Novel 24F Aspiration/Guide Catheter - Horowitz, Michael Bruce; Bobo, Benjamin; Repko, Brandon; Le, Hieu (Cardiology and Cardiovascular Medicine, 2024)
This report documents the performance of a novel 24F aspiration/guide catheter (8 mm OD; 7.1 mm ID) manufactured by Retriever Medical Inc. (Las Vegas, Nevada, USA) using in vitro and in vivo modeling. Results demonstrated excellent trackability with ability to navigate tortuous anatomy and serial 90 - 180 degree turns. At a radius of curvature of 6 mm, catheter ovalization (lumen collapse) was not encountered while it was encountered in a similar 24F catheter that at baseline (when positioned straight) had an inner ID 0.2 mm smaller than the novel catheter studied in this report. The capability of the Retriever Medical,Inc 24 F catheter to navigate tortuous anatomy without associated luminal collapse makes it an ideal conduit for thrombus aspiration with and without simultaneous use of a transaxially delivered mechanical thrombectomy device.